H. ALIYEV: "EDUCATION IS THE FUTURE OF THE NATION" - Asadova Sevinj Sabir (Progress in Science, 2023)
The tradition of H. Aliyev is continued today, and the work done by Mr. Ilham Aliyev and Mrs. Mehriban Aliyeva with the support of the H. Aliyev Foundation in the direction of education development is worthy of appreciation. Let's unite under the flag of independent Azerbaijan and do everything we can to educate and educate our people.